Some Notes on Normality Criteria of Meromorphic Functions (Communications in Mathematical Research, 2021)
In this paper, we study the normality of families of meromorohic functionsrelated to a Hayman conjecture. We prove that the conditions in Hayman conjectureand in other criterions can be relaxed. The results in this paper improve some previousresults.
Keywords: meromorphic function; shared value; normal criterion.